Impact and Prevalence of Musculoskeletal Injuries due to Accident at Work in Brazil, 2015-2020 (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: musculoskeletal injuries; accidents at work; injuries due to accident at work; workers